Darwinian Evolution of Intelligence - Phillips, J. C. (Frontiers in Bioinformatics, 2022)
Intelligence is often discussed in terms of neural networks in the cerebral cortex, whose evolution has presumably been influenced by Darwinian selection. Here we present molecular evidence that one of the many kinesin motors, KIF14, has evolved to exhibit a special feature in its amino acid sequence that could improve neural networks. The improvement is quantified by comparison of NIF14 sequences for 12 species. The special feature is level sets of synchronized hydrophobic extrema in water wave profiles based on several hydropathic scales. The most effective scale is a new one based on fractals indicative of approach of globular curvatures to self-organized criticality, which summarizes evolutionary trends based on intelligent design.